(untitled) (Muitas Vozes, 2024)
The question regarding the definition of what constitutes or does not constitute a case of authorship in literary texts is a rather long debate that continues as a generator of great controversies. However, what can be seen is that such concepts were produced from a place of being able to settle down - intellectual, white and European men - despite not having their places of enunciation duly marked. Roland Barthes, as one of the great exponents working on the notions of authorship from a structuralist paradigm, argues that writing would rely on a supposed neutrality of language and the dissociation of the body and history of the one who writes, thus maintaining that the beginning of writing would be marked by the death of the author. Black women’s writing openly denounces the impossibility of a language that proposes to be neutral, opening a powerful space for tensioning and questioning the canon and hoping for the construction of a decolonial, ethical, aesthetic and political paradigm.